A Matter of Feelings: Mediators’ Perceptions of Emotion in Hierarchical Workplace Conflicts - Kalter, Meriem; Bollen, Katalien; Euwema, Martin; Verbeke, Alain-Laurent (Frontiers in Psychology, 2021)
Emotions play a central role in the process of conflict and resolution. For a mediator, it is important to recognize emotions correctly and act upon them. Whether interventions are appropriate depends to a large extent on the ability of mediators to accurately perceive the emotions of conflict parties. Particularly in hierarchical labor conflicts, this can be challenging, since subordinates tend to hide emotions while supervisors tend to express them. In this study, we investigated if subordinates and supervisors differ in their emotional experience during mediation and whether mediators perceive these emotions accurately. To this end, we compared the extent to which disputants experienced certain emotions with the extent to which mediators perceived these emotions. Data were collected through surveys of mediation clients and mediators in hierarchical labor conflicts in the Netherlands. As expected, subordinates experienced a higher level of negative emotions during the mediation than supervisors did. Positive emotions, however, were experienced to a similar extent by both supervisors and subordinates in mediation. Mediators perceived supervisors’ emotions more accurately than they did subordinates’ emotions. While supervisors’ emotions were positively related with mediators’ perceptions, this was not the case for subordinates’ emotions. Furthermore, mediators were more accurately perceiving supervisors’ negative emotions than their positive emotions. Implications for mediation theory and practice are discussed.